Cannabinoid Effect and Safety in Spasticity Following Stroke: A Double-Blind Randomized Placebo-Controlled Study - Marinelli, Lucio; Puce, Luca; Mori, Laura; Leandri, Massimo; Rosa, Gian Marco; Currà, Antonio; Fattapposta, Francesco; Trompetto, Carlo (Frontiers in Neurology, 2022)
Background Nabiximols is a cannabis-based drug to treat spasticity-associated symptoms currently approved for patients with multiple sclerosis only. Cannabinoids are useful in an increasing number of medical conditions but may bear an increased risk for cardiovascular events. SativexStroke is a double-blind randomized placebo-controlled crossover monocentric clinical trial investigating the efficacy and safety of nabiximols in patients with spasticity following stroke. Methods Patients were treated with nabiximols oromucosal spray or placebo and assessed before and after two phases of 1-month duration each. Cardiovascular safety was assessed before and during the trial. Primary endpoints were changes in spasticity numeric rating scale scores and electromyographic recording of the stretch reflex in affected wrist flexors. Secondary outcome measures were numeric rating scale scores for pain, sleep and bladder function, the number of daily spasms and clinical assessment of spasticity with the modified Ashworth scale. The study was registered with the EudraCT number 2016-001034-10. Results Between May 2, 2018, and February 20, 2020, 41 patients entered the study. Seven patients did not complete the study, so 34 were included in the analysis. Two serious adverse events occurred, but none related to cardiovascular function. Primary and secondary efficacy outcome measures did not change from baseline during nabiximols treatment relative to placebo. Conclusion This study suggests that nabiximols use is probably safe in stroke patients, therefore cannabinoid usefulness may be further investigated. The lack of nabiximols effect could be related to low pain levels in recruited patients or different spasticity mechanisms between post-stroke and multiple sclerosis patients. Similarly, a beneficial effect of nabiximols could have emerged if more patients with a higher level of spasticity at baseline were recruited. Clinical Trial Registration https://www.clinicaltrialsregister.eu/ctr-search/trial/2016-001034-10/IT.